Aegaean Concepts in the Eastern Hallstatt Culture - Potrebica, Hrvoje (2007)
The author discusses some of the religious features in Central Europe and the Balkans that may be perceived as related to Aegean religious concepts. Several models were suggested to explain those similarities with special reference to cultural transfer induced by exchange of prestigious objects between elites in different societies.
Projekt MZOS
Projekt MZOS
ENG